2020
DOI: 10.1039/d0ay00165a
|View full text |Cite
|
Sign up to set email alerts
|

An indirect Raman spectroscopy method for the quantitative measurement of respirable crystalline silica collected on filters inside respiratory equipment

Abstract: A new Raman method for respirable crystalline silica that is capable of measuring concentrations below the limits of detection of current analytical methodology and worker exposures when wearing respirators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…X-ray diffraction (XRD) and FTIR are two analytical techniques that are commonly employed for the measurement of aerosol sampling filters containing RCS (Pickard et al, 1985;HSE, 2014). Raman spectroscopy is also available (Zheng et al, 2018;Stacey et al, 2020) but is a relatively new technique for this type of analysis,…”
Section: What's Important About This Paper?mentioning
confidence: 99%
“…X-ray diffraction (XRD) and FTIR are two analytical techniques that are commonly employed for the measurement of aerosol sampling filters containing RCS (Pickard et al, 1985;HSE, 2014). Raman spectroscopy is also available (Zheng et al, 2018;Stacey et al, 2020) but is a relatively new technique for this type of analysis,…”
Section: What's Important About This Paper?mentioning
confidence: 99%
“…Moving to a lower magnification objective to increase the collection of laterally scattered photons will not improve the intensity of the Raman scatter, because the lower magnification with low numerical aperture has a smaller angle of light collection. [45] Fine grains studied in this work are smaller than those previously investigated and will scatter photons in a relatively localised area close to the particles' surface, which will be efficiently collected by the detector when using the current optics applied by the method proposed by Stacey et al [24] ; that is, the proportion of laterally dispersed photons is small for particles in this study. These conditions may account for the plateau for Raman band intensity observed in this research, for fractions of quartz particles with median diameters between 1 and 7 μm.…”
Section: Response Due To Particle Size and Sample Depthmentioning
confidence: 93%
“…The number of photons counted could increase with particle size when the detector area was much larger than the illumination area (×4.2) but could also decrease when the two areas were more similar (×1.6) because the laterally scattered photons on larger particles were not detected as efficiently. Previous method development work showed a decrease in measurement sensitivity when using the quartz reference material with the largest particle size (Quin B), [24] suggesting that the instrument arrangement proposed for the measurement method was not efficiently collecting the laterally scattered photons for the very largest particles in this instance. In this research, reported herein, the minimum area of the focused spot was 4.5 μm 2 , which is slightly less the than median diameter of the particles of Quin B (7 μm).…”
Section: Response Due To Particle Size and Sample Depthmentioning
confidence: 94%
See 2 more Smart Citations